Glucagon-producing cells are increased in Mas-deficient mice - Janaína Felix Braga; Daniela Ravizzoni Dartora; Natalia Alenina; Michael Bader; Robson Augusto Souza Santos (Endocrine Connections, 2017)
It has been shown that angiotensin(1–7) (Ang(1–7)) produces several effects related to glucose homeostasis. In this study, we aimed to investigate the effects of genetic deletion of Ang(1–7), the GPCR Mas, on the glucagon-producing cells. C57BL6/N Mas−/− mice presented a significant and marked increase in pancreatic α-cells (number of cells: 146 ± 21 vs 67 ± 8 in WT; P < 0.001) and the percentage per islet (17.9 ± 0.91 vs 12.3 ± 0.9% in WT; P < 0.0001) with subsequent reduction of β-cells percentage (82.1 ± 0.91 vs 87.7 ± 0.9% in WT; P < 0.0001). Accordingly, glucagon plasma levels were increased (516.7 ± 36.35 vs 390.8 ± 56.45 pg/mL in WT; P < 0.05) and insulin plasma levels were decreased in C57BL6/N Mas−/− mice (0.25 ± 0.01 vs 0.31 ± 56.45 pg/mL in WT; P = 0.02). In order to eliminate the possibility of a background-related phenotype, we determined the number of glucagon-producing cells in FVB/N Mas−/− mice. In keeping with the observations in C57BL6/N Mas−/− mice, the number and percentage of pancreatic α-cells were also significantly increased in these mice (number of α-cells: 260 ± 22 vs 156 ± 12 in WT, P < 0.001; percentage per islet: 16 ± 0.8 vs 10 ± 0.5% in WT, P < 0.0001). These results suggest that Mas has a previously unexpected role on the pancreatic glucagon production.